Recovery effects of repeated exposures to normobaric hyperoxia on local muscle fatigue - Yokoi, Y.; Yanagihashi, R.; Morishita, K.; Goto, N.; Fujiwara, T.; Abe, K. (The Journal of Strength and Conditioning Research, 2014)
Reported recovery effects of hyeroxia are conflicted. This study aimed to identify the effects and the mechanisms of normobaric hyperoxia on the recovery of local muscle fatigue, which is the most commonly encountered form of fatigue both daily and in training and competitions. Twelve male subjects performed 3 × 3 × no less than 30 seconds of isometric quadriceps exercise at 70% of maximum voluntary isometric contraction (MVIC) separated by two 15-minute recovery sessions under 1 of 2 different atmospheric oxygen concentrations, one in normoxia (NOX; 20.9% O2) and another in hyperoxia (HOX; 30.0% O2). To assess the degree of fatigue and recovery, 4 parameters were used; MVIC, endurance time to exhaustion, blood lactate, and perceived exertion measured by a visual analog scale (VAS). Maximum voluntary isometric contraction improved an average by approximately 14% in HOX compared with NOX at the conclusion of the second recovery session. However, this was not associated with changes in other parameters because changes in endurance time, blood lactate, and VAS during the trials were similar. Based on our findings, we conclude that 2 sets of 15-minute recovery session in normobaric hyperoxia are effective for restoring MVIC from local muscle fatigue induced by intermittent intense exercises. For quicker recovery, athletes are recommended to repeat 15-minute recovery process under 30.0% hyperoxia.